^{-1}(x). For the equation f(x)=2e

^{3x}+1

find the inverse, f^{-1}(x). For the equation f(x)=2e^{3x}+1

Tutors, sign in to answer this question.

Philip P. | Effective and Affordable Math TutorEffective and Affordable Math Tutor

f(x) = 2e^{3x}+1

y = 2e^{3x}+1

To find the inverse function, f^{-1}(x), swap the x's and y's and solve for y:

x = 2e^{3y}+1

x-1 = 2e^{3y}

(1/2)(x-1) = e^{3y}

ln[(1/2)(x-1)] = 3y [take the ln of both sides]

(1/3)(-ln(2)+ln(x-1)) = y [ln(1/2) = ln(2^{-1}) = -ln(2), ln(ab) = ln(a) + ln(b)]

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.